Omicron: What Makes the Latest SARS-CoV-2 Variant of Concern So Concerning? - Jung, Christoph; Kmiec, Dorota; Koepke, Lennart; Zech, Fabian; Jacob, Timo; Sparrer, Konstantin M. J.; Kirchhoff, Frank (Journal of virology, 2022)
Emerging strains of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the coronavirus disease 2019 (COVID-19) pandemic, that show increased transmission fitness and/or immune evasion are classified as “variants of concern” (VOCs). Recently, a SARS-CoV-2 variant first identified in November 2021 in South Africa has been recognized as a fifth VOC, termed “Omicron.” What makes this VOC so alarming is the high number of changes, especially in the viral Spike protein, and accumulating evidence for increased transmission efficiency and escape from neutralizing antibodies. Emerging strains of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the coronavirus disease 2019 (COVID-19) pandemic, that show increased transmission fitness and/or immune evasion are classified as “variants of concern” (VOCs). Recently, a SARS-CoV-2 variant first identified in November 2021 in South Africa has been recognized as a fifth VOC, termed “Omicron.” What makes this VOC so alarming is the high number of changes, especially in the viral Spike protein, and accumulating evidence for increased transmission efficiency and escape from neutralizing antibodies. In an amazingly short time, the Omicron VOC has outcompeted the previously dominating Delta VOC. However, it seems that the Omicron VOC is overall less pathogenic than other SARS-CoV-2 VOCs. Here, we provide an overview of the mutations in the Omicron genome and the resulting changes in viral proteins compared to other SARS-CoV-2 strains and discuss their potential functional consequences.